Study of structural, optical and magnetic properties of cobalt doped ZnO nanorods - Chanda, Anupama; Gupta, Shipra; Vasundhara, M.; Joshi, Shalik R.; Mutta, Geeta R.; Singh, Jai (Royal Society of Chemistry, 2017)
Cobalt doped zinc oxide nanoparticles (NPs) and nanorods (NRs) were synthesized by a simple chemical method. An increase in the formation of nanorods with an increase in cobalt doping is found to occur from scanning electron microscopy and transmission electron microscopy studies. Powder X-ray diffraction, high-resolution transmission electron microscopy, and selected area electron diffraction confirm the formation of a wurtzite crystal structure of ZnO. Shifting and broadening of the bands at 437 cm-1 and 579 cm-1 in the micro-Raman study of Co-doped ZnO nanostructures indicates the incorporation of Co in ZnO. Shifting of the absorption edge to lower wavelength and blue shift of the band gap is observed in UV-visible spectra of Co-doped ZnO samples. Field-dependent magnetization measurements exhibit diamagnetic behavior down to 2 K in the case of ZnO whereas Co-doped ZnO samples show coexistence of superparamagnetic and ferromagnetic behavior at room temperature and at 2 K. The observed ferromagnetism may have originated due to the exchange interaction between the localized d electrons in Co2+ atoms and free carriers generated due to Co-doping as well as due to cobalt clustering in the Co-doped samples.
Keywords: Cobalt; Zinc oxide; Nanorods; Scanning electron microscopy; Ferromagnetism